Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1063/5.0003575
|View full text |Cite
|
Sign up to set email alerts
|

A compact electron source for the dielectric laser accelerator

Abstract: In this work, we design and demonstrate a compact electron source that combines an integrated silicon nanotip photoemitter with a compact silicon-based electrostatic lens. The lens simultaneously accelerates electrons to 30 keV and focuses the resulting beam to a 0.4 μm (RMS) beam diameter with 62 pm-rad normalized emittance at a distance of 20 mm from the cathode. The compact nature of this lens provides a compelling source for dielectric laser accelerator (DLA) beamlines, ultrafast electron diffraction, or u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…To create them, it is planned to use an electronoptical system with a needle cathode irradiated by the light of a titanium-sapphire laser. A similar electron gun was demonstrated in paper [29] on direct laser acceleration of electrons in a comb-type dielectric accelerating structure. The use of the same laser pulse for both cathode irradiation and generating the terahertz radiation significantly simplifies the synchronization of electron bunches with a terahertz field in the accelerating structure.…”
Section: Scheme Of the Experiments On Acceleration Of Electron Bunches By Ultrashort Pulses Of Terahertz Radiationmentioning
confidence: 76%
“…To create them, it is planned to use an electronoptical system with a needle cathode irradiated by the light of a titanium-sapphire laser. A similar electron gun was demonstrated in paper [29] on direct laser acceleration of electrons in a comb-type dielectric accelerating structure. The use of the same laser pulse for both cathode irradiation and generating the terahertz radiation significantly simplifies the synchronization of electron bunches with a terahertz field in the accelerating structure.…”
Section: Scheme Of the Experiments On Acceleration Of Electron Bunches By Ultrashort Pulses Of Terahertz Radiationmentioning
confidence: 76%
“…A typical 200 keV system will have roughly a 1 meter distance from the electron source to the DLA. Efforts have been made to produce a a more compact electron injector by using an electro-static immersion lens built into the electron source region to directly focus the beam coming off of a nanotip source [24]. This allows the nanotip emitter to be re-imaged into a DLA device in less than 25 mm distance at 96 keV beam energy as shown in Fig.…”
Section: Ultra-low Emittance Injectormentioning
confidence: 99%
“…Like many groundbreaking technologies, OFC is a breaking technique and has given rise to substantial advances in many research fields. [9] It provides a broadband waveform with well-defined phase coherence and is being explored for a myriad of possible applications such as attosecond pulse generation, [10] atomic clock networks, [11] and precision spectroscopy, [12] distance measurements, [13] etc. More recently, it has been suggested that OFC could provide stable physical channels and information carriers for multicarrier transmission, where the effective nonlinearity correction (NLC) can be performed at both transmitter and receiver side, thus overcoming the nonlinear capacity limit in the long-haul fiber communication.…”
Section: Introductionmentioning
confidence: 99%